Radionuclide therapy of metastatic prostate cancer - Kratochwil, Clemens; Haberkorn, Uwe; Giesel, Frederik L. (Seminars in nuclear medicine, 2019)
The current mainstay of treatment in metastatic prostate cancer is based on hormonal manipulations. Standard androgen deprivation therapy and novel androgen axis drugs are commonly well tolerable and can stabilize metastatic hormone-sensitive prostate cancers for years. However, metastatic castration-resistant prostate cancer is still challenging to treat. Except taxanes, prostate cancer presents intrinsic resistance against conventional chemotherapies. The typically elderly patient population excludes more aggressive treatment regimens. First clinical trials evaluating immunotherapy or tyrosine-kinase-inhibitors against prostate cancer failed. In contrast, prostate cancer can be radiosensitive and external beam radiotherapy is effective in localized prostate cancer, thus providing a good rationale for the use of systemic radiopharmaceuticals in the metastatic setting. Beta-particle emitting “bone-seekers” have a long history and are effective as analgesics but do not improve survival because they are limited by red-marrow dose. Alpha emitting 223Radium can be used in a dose that prolongs survival but is restricted to bone-confined patients. Currently radiolabeled high-affinity ligands to the prostate-specific membrane antigen are in clinical evaluation. While radioimmunotherapy approaches were limited by the long circulation time and slow tumor-accumulation of antibodies, low molecular weight PSMA-specific ligands offer an approx. ten-fold improved tumor to red-marrow ratio in comparison to the unspecific bone-seekers. Early clinical studies demonstrate that regarding surrogate markers, such as >50% PSA reduction (60%) and radiologic response (80%), PSMA-therapy exceeds the antitumor activity of all approved or other recently tested compounds; for example, PSA-response was only observed in approx. a total of 10% of patients treated with ipilimumab, sunitinib, cabozantinib, or xofigo, respectively and in approx. 30, 40, 50% of patients treated with abiraterone, cabazitaxel, or enzalutamide. Also progression free and overall survivals of these single-arm studies appear promising when compared to historical controls. Consecutively, the first PSMA-RLT recently advanced into phase-3 (177Lu-PSMA-617; VISION-trial). Future developments aim to avoid off-target radiation by ligand-optimization and to outperform the antitumor activity of beta-emitter PSMA-RLT by labeling with highly focused, high energy transferring alpha-nuclides; however the latter potentially also increasing the risk of side-effects and additional early phase studies are needed to improve treatment protocols. Academically clinical research is developing prognostic tools to improve treatment benefit by selecting the most appropriate patients in advance.
Gesehen am 06.08.2019